EFFECTS OF LAYER AGE AND EGG WEIGHT ON EGG QUALITY TRAITS OF - JAPANESE QUAILS (Coturnix coturnix japonica); #; #; N. T. H. Nhan; L. T. T. Lan; N. T. K. Khang; P. N. Du; T. N. Dung; N. T. Ngu (Journal of Animal and Plant Sciences, 2018)
The study was carried out to analyze the impact of layer age and egg weight on egg quality characteristics and further assess the correlation between these traits in Japanese quail eggs. In total, 295 quail layers starting from 10 weeks old were used in the experiment and 2,360 eggs were examined for quality evaluation. Bird age was grouped in every four weeks of laying period and eggs were categorized according to their weights (small, medium, large and extra-large). It th th was shown that eggs were smaller at 10 week of age (11.43 g) and gradually increased in weight till week 26 (11.61 g) th and 30 (11.62 g). Quail age influenced all of egg internal characteristics examined (P<0.001) while egg weight was significantly associated with most of albumen and yolk traits, except for albumen height, yolk index and yolk color. There existed both negative and positive correlations among these traits as well. The obtained results indicated that advanced age had increasing egg weight but lesser redness in egg yolk color, and larger eggs provided greater values of albumen weight, albumen ratio, yolk height, yolk weight but reduced Haugh unit. influence other external and internal egg characteristics
Keywords: egg weight; egg quality; Japanese quail; layer age.